SIYANDA NDLOVU 25 March 1982 – 5 April 2010 - Hayes, Grahame (PINS-Psychology in Society, 2025)
Siyanda Ndlovu, along with some friends and colleagues, had gone down to the coast (just south of Durban) for the easter weekend, to do some work and relaxing. The work that he was doing was writing a book review for PINS (the one that follows). He was intending to talk to me about the review when he got back to Durban, as it had got “somewhat unwieldy”. Our book reviews are usually in the 1 500 to 2 000 words range, and his was already over 4 000 words! What I would have told him is that he should either drastically cut his review to meet the 1 500 – 2 000 word limit, or else extend it as a review article, which would also entail submitting it for anonymous review.